Herbal Plant Education and Hydroponic Training of Vertical and Wick System in Limited Space - Andini, Ary; Prayekti, Endah; Romdloni , Muhammad Afwan; Rhomadhoni , Muslikha Nourma; Sofaria Munir, Ratna (Community Development Journal, 2024)
The program "Empowering the Community of Simo Angin-Angin Village, Sidoarjo through the Use of Natural Materials to Achieve Health Independence" was implemented at the Simo Angin-Angin Village Hall, Krian District, Sidoarjo Regency in May-June 2023. This Community Empowerment Program (Community Service) carries a preventive and consists of a series of activities, including counseling about the use of natural materials based on the recommendations of the Koran, considering that the majority of Simo Angin-Angin village residents are Muslim. This activity also includes training in farming using the hydroponic method. The aim of this program is to strengthen health independence in Simo Angin-Angin Village in order to improve collective welfare. The Community Service program in Simo Angin-Angin Village was attended by 22 participants, consisting of health cadres and the general public. The implementation is divided into 2 stages, namely counseling regarding the Black Cumin herbal plant and training regarding vertical hydroponic procedures, as well as the use of plastic bottles with the Wick system. The evaluation results showed that participants' understanding was very good, with 95% of them achieving a score of 100, while 5% obtained a score of 80. The evaluation results of participant satisfaction with the implementation of the extension showed very good scores for the topic material and delivery of the material by resource persons on herbal plant education and hydroponic training. This Community Service activity provides skills for the community to grow crops on narrow land using a hydroponic system